Acoustic metaporous layer with composite structures for perfect and quasi-omnidirectional sound absorption. (1st September 2019) - Fang, Yi; Zhang, Xin; Zhou, Jie; Guo, Jingwen; Huang, Xun
Abstract: To enhance the sound absorption capability of porous materials, an acoustic metaporous layer is proposed. The sound absorption is enhanced based on the capability of reflected wave manipulation using the metaporous layer. The designed structure is periodic and one period of the metaporous layer contains four slits filled with the porous materials and embedded partitions. The partitions in the four slits are designed to form different phase responses of reflected waves, so that a linear phase gradient is generated within one period length. The phase gradient has a deciding influence on the reflected wave manipulation. The capability of manipulating the reflected waves is demonstrated numerically and experimentally. When the period is smaller than a half of wavelength, high-order reflected waves carrying the most energy are prevented from radiating into an acoustic far field at omni-directional incidence, resulting in an enhancement of oblique-incidence sound absorption compared with the uniform porous layer with the same thickness. The study shows that the remarkable enhancement of sound absorption can be obtained even though the phase gradient is not uniformly distributed, making the metaporous layer effective in a specific frequency range. The study provides a method to design non-uniform sound absorbers.